PERINATAL COMPLICATIONS FOLLOWING EXCISIONAL TREATMENT OF CERVICAL DYSPLASIA - Sparic, Radmila M; Anđić, Mladen; Plešinac, Vera; Tomašević, Đina; Marjanović Cvjetićanin, Mirjana; Mostić Stanišić, Danka (Medical Research, 2023)
Cervical cancer is one of the most common malignant tumors in women. Mass screenings have significantly decreased its incidence, while causing an increase in precancerous cervical lesions that are mainly diagnosed in women of the reproductive age who still have not fulfilled their reproductive goals. The aim of surgical treatment of these premalignant lesions is to prevent the development of cervical cancer, with minimal risks to the reproductive function. The most important perinatal complications are preterm delivery, usually coupled with preterm premature rupture of the membranes, and chorioamnionitis. This results in prematurity with low birth weights, which can further result in increased neonatal morbidity and mortality. Data on the incidence of spontaneous miscarriages in treated women are non-consistent, however, it is believed that the incidence is higher in the second trimester. Possible predictors of complications are the amount of excised tissue, type of excision technique, age at the time of surgery and length of period between treatment and conception. An additional risk factor for perinatal complications is the re-excision of the cervix. The risk for perinatal complications is the highest after cold knife conization, followed by laser conization, and the lowest risk is after LOOP excision - which is primarily explained by the variations in the cone size. Having in mind that not all precancerous cervical lesions progress to cancer and that all types of excision treatments are associated with an increased incidence of perinatal complications, an adequate approach would entail primarily well-selected patients, i.e., treatment of only those women who are at real risk of developing cancer. The surgical treatment must be adapted to provide minimal risks for perinatal complications, maximal oncologic safety, and minimal risk for residual and/or recurring disease during a woman’s lifespan.